When Should Genome Researchers Disclose Misattributed Pahentage?. Issue 4 (11th February 2015) - Mandava, Amulya; Millum, Joseph; Berkman, Benjamin E.
Abstract As analytic tools for genomic sequencing improve, biomedical research will increasingly use this method to draw inferences based on comparisons between the genetic data of a set of individuals thought to be related to each other. Cases in which genomic sequencing will be very useful include those in which a child has a rare or undiagnosed disease that might have an underlying genetic etiology. Researchers will be able to sequence the pediatric proband and both parents to compare their genomes in hopes of finding novel variants that point toward a diagnosis and perhaps to treatment. However, researchers are sure to discover that, in a growing number of cases, the assumed biological relationships between the individuals do not actually exist. Consequently, they will have to grapple with decisions about whether to return incidental findings of misattributed genetic parentage on a much larger scale than ever before. While we make no normative claims about whether individuals ought to value genetic relationships, the disclosure of information about misattributed parentage has the potential to affect familial relationships and notions of personal identity in many ways. Researchers need a decision‐making framework about disclosing this information that accounts for nonclinical factors alongside factors that the incidental findings literature already emphasizes as relevant. We argue that nondisclosure should be the default position for researchers. We begin by assessing the limited guidance that can be found in the literature on incidental research findings and on disclosure of misattributed parentage in the clinical setting. We then sketch the normative argument that underlies our position, providing a taxonomy of the possible harms and benefits of disclosure. We close by considering three objections: that nondisclosure may cause false beliefs in participants, that researchers may have relationships of trust with their participants that entail a duty to disclose, and that participant preferences should be solicited and followed. We close by suggesting ways in which the consent process could minimize possible harms related to nondisclosure.